2008
DOI: 10.3171/jns/2008/108/6/1132
|View full text |Cite
|
Sign up to set email alerts
|

Screening for brain aneurysm in the Familial Intracranial Aneurysm study: frequency and predictors of lesion detection

Abstract: Object-Approximately 20% of patients with an intracranial saccular aneurysm report a family history of intracranial aneurysm (IA) or subarachnoid hemorrhage. A better understanding of predictors of aneurysm detection in familial IA may allow more targeted aneurysm screening strategies. Methods-TheFamilial Intracranial Aneurysm (FIA) study is a multicenter study, in which the primary objective is to define the susceptibility genes related to the formation of IA. First-degree relatives (FDRs) of those affected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 18 publications
1
58
0
9
Order By: Relevance
“…These are slightly higher than those reported in non-ADPKD patients with one (2.6% to 5.8%) or two or more (3.9% to 14%) first-degree family members with a history of IA or SAH (19). The 16% to 21% prevalence in ADPKD patients with a family history of IA or SAH is similar to that observed in non-ADPKD individuals with two or more first-degree relatives with a history of IA or SAH plus a personal history of smoking or hypertension (approximately 19%) (20).…”
Section: Discussionmentioning
confidence: 60%
“…These are slightly higher than those reported in non-ADPKD patients with one (2.6% to 5.8%) or two or more (3.9% to 14%) first-degree family members with a history of IA or SAH (19). The 16% to 21% prevalence in ADPKD patients with a family history of IA or SAH is similar to that observed in non-ADPKD individuals with two or more first-degree relatives with a history of IA or SAH plus a personal history of smoking or hypertension (approximately 19%) (20).…”
Section: Discussionmentioning
confidence: 60%
“…[3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation. 10,11 All these evidence fortified the roles of genetic factors in the pathogenesis of IA.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Smaller studies have suggested that screening of those with 1 first-degree relative with aSAH may be justified as well, but it is far less clear whether patients who underwent treatment for a previous aSAH require ongoing screening. 51,52 In the Cerebral Aneurysm Rerupture After Treatment (CARAT) study, recurrent aSAH was predicted by incomplete obliteration of the aneurysm and occurred a median of 3 days after treatment but rarely after 1 year. 53 Repeated noninvasive screening at later times may not be cost-effective, increase life expectancy, or improve quality of life in unselected patients.…”
Section: Applying Classification Of Recommendation and Level Of Evimentioning
confidence: 99%